Colour matters: the effects of lensing on the positional offsets between optical and submillimetre galaxies in Herschel-ATLAS - Bourne, N.; Maddox, S.J.; Dunne, L.; Dye, S.; Eales, S.; Hoyos, C.; Gonzalez-Nuevo, J.; Smith, D.J.B.; Valiante, E.; de Zotti, G.; Ivison, R.J.; Rowlands, K. (Oxford University Press, 2014)
We report an unexpected variation in the positional offset distributions between Herschel-Astrophysical Terahertz Large Area Survey (H-ATLAS) submillimetre (submm) sources and their optical associations, depending on both 250-μm signal-to-noise ratio and 250/350-μm colour. We show that redder and brighter submm sources have optical associations with a broader distribution of positional offsets than would be expected if these offsets were due to random positional errors in the source extraction. The observation can be explained by two possible effects: either red submm sources trace a more clustered population than blue ones, and their positional errors are increased by confusion, or red submm sources are generally at high redshifts and are frequently associated with low-redshift lensing structures which are identified as false counterparts. We perform various analyses of the data, including the multiplicity of optical associations, the redshift and magnitude distributions in H-ATLAS in comparison to HerMES, and simulations of weak lensing, and we conclude that the effects are most likely to be explained by widespread weak lensing of Herschel-SPIRE sources by foreground structures. This has important consequences for counterpart identification and derived redshift distributions and luminosity functions of submm surveys.